The Perception of Visual Acuity to relieve Fatigue Symptoms From Technological Devices in the Digital Age - Changthum, Prangthong; Porncharoen, Ratrhai (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
Nowadays, the world has been rapidly changing trend, and its impact continuously until the present. In 1970, the world was driven by development. Besides, the trend of global social transformation is characterized by a dynamic that generates relentless movements. Therefore, information technology is essential in economic development. Digital devices have been fulfilling human beings. However, using digital devices with misuse of gestures may affect the quality of life, especially for performance degradation. Interestingly, the study revealed that 90% of digital device users using devices for 16 hours per day. The mentioned behavior affects visual focusing and weakens the visual perception process, resulting in Cumulative Trauma Disorder. Especially symptoms caused by heavy eyesight for a long time called Visual Fatigue may affect life quality. For this reason, the mentioned problem is a silent threat that is undermining the global population. The study of Visual Perception theory is an alternative science-based on specialized medical techniques in Ophthalmology. When applied to the visual management process through training methods to help relax eye muscles. Besides, the symptoms of fatigue affect characteristics of determining the senses and movement direction. The direction determination process is similar to the principle of eye massage, resulting in the relief of chronic injuries, a natural eye restoration (Natural Vision) by mediating the natural process of the ophthalmic experience (Sense Organs) external stimuli. In other words, it can preserve eyes from digital devices that are then developed and technology and prevalent in the digital age.